Hernia of Umbilical Cord: Report of Three Unusual Cases - Bilal Mirza; Afzal Mirza; Imran Hashim; Muhammad Saleem (EL-Med-Pub, 2015)
Congenital hernia of umbilical cord is a less frequent entity in newborns and occasionally associated with other maladies. Herein, we report three cases of hernia of umbilical cord. First case was associated with in-utero evisceration of entire small bowel through the presumably ruptured hernia of umbilical cord and other two cases had associated patent vitellointestinal duct (PVID). All of the cases were managed successfully.